Comparing ray-theoretical and finite-frequency teleseismic traveltimes: implications for constraining the ratio of S-wave to P-wave velocity variations in the lower mantle - Chaves, CAM; Ritsema, J; Koelemeijer, P (Oxford University Press, 2020)
A number of seismological studies have indicated that the ratio R of S-wave and P-wave velocity perturbations increases to 3–4 in the lower mantle with the highest values in the large low-velocity provinces (LLVPs) beneath Africa and the central Pacific. Traveltime constraints on R are based primarily on ray-theoretical modelling of delay times of P waves (ΔTP) and S waves (ΔTS), even for measurements derived from long-period waveforms and core-diffracted waves for which ray theory (RT) is deemed inaccurate. Along with a published set of traveltime delays, we compare predicted values of ΔTP, ΔTS, and the ΔTS/ΔTP ratio for RT and finite-frequency (FF) theory to determine the resolvability of R in the lower mantle. We determine the FF predictions of ΔTP and ΔTS using cross-correlation methods applied to spectral-element method waveforms, analogous to the analysis of recorded waveforms, and by integration using FF sensitivity kernels. Our calculations indicate that RT and FF predict a similar variation of the ΔTS/ΔTP ratio when R increases linearly with depth in the mantle. However, variations of R in relatively thin layers (< 400 km) are poorly resolved using long-period data (T > 20 s). This is because FF predicts that ΔTP and ΔTS vary smoothly with epicentral distance even when vertical P-wave and S-wave gradients change abruptly. Our waveform simulations also show that the estimate of R for the Pacific LLVP is strongly affected by velocity structure shallower in the mantle. If R increases with depth in the mantle, which appears to be a robust inference, the acceleration of P waves in the lithosphere beneath eastern North America and the high-velocity Farallon anomaly negates the P-wave deceleration in the LLVP. This results in a ΔTP of about 0, whereas ΔTS is positive. Consequently, the recorded high ΔTS/ΔTP for events in the southwest Pacific and stations in North America may be misinterpreted as an anomalously high R for the Pacific LLVP.